2021
DOI: 10.1182/blood-2021-153309
|View full text |Cite
|
Sign up to set email alerts
|

Over-Expression of CRLF2 By Flow Cytometry (FC) Impacts on Overall Survival (OS) in Mexican Patients with Acute Lymphoblastic Leukemia (ALL)

Abstract: Introduction: "Philadelphia like" ALL has been related to poor prognosis. CRLF2 over-expression (cytokine receptor like factor-2) has been found in up to 50% of patients with Philadelphia-like ALL and its expression can be measured by Flow Cytometry (FC). CRLF2 over-expression is more common in Hispanic population (45-68%) however, there is no current recommendation in using it as a prognostic marker. Objectives: Find the prevalence of CRLF2 overexpression measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“… 6 Another report in Mexico showed that 41.3% of adults diagnosed with ALL have CRLF2 overexpression, via flow cytometry, and this was associated with worse outcomes. 15 These results support the hypothesis that the population in Mexico and Central America has a more aggressive biology of the disease and could explain the increased risk of relapse in this population.…”
Section: Discussionsupporting
confidence: 80%
“… 6 Another report in Mexico showed that 41.3% of adults diagnosed with ALL have CRLF2 overexpression, via flow cytometry, and this was associated with worse outcomes. 15 These results support the hypothesis that the population in Mexico and Central America has a more aggressive biology of the disease and could explain the increased risk of relapse in this population.…”
Section: Discussionsupporting
confidence: 80%